Teori dan aplikasi Rukhsah ketika solat: khas untuk jururawat dan pesakit - Mohamad Ismail, Mohamad Firdaus; Mohd Arifin, Siti Roshaidai (2019)
Working in a Muslim country like Malaysia requires nurses to have adequate knowledge and input on how Islam allows some level of adjustment (Rukhsah) for the sick people to perform Solah. To do so, nurses should be empowered with ability, knowledge and skills to assist patients under their care to perform Solah, hence they are able to deliver the knowledge effectively. However, it is well documented that nurses have overlooked the spiritual dimension in their care. To date, there is a lack of specific training, coaching, and teaching that formally educate the nurses on how to assist their patients in performing Solah. Consequently, nurses are not sure of how to assist patients in performing Solah while they are admitted to the ward. This book provides a guidelines for both nurses and patients on performing Solah while in the hospital. It is hoped that this book will will enhance Muslim patients’ ability and confidence in continuing to perform their Solah while in sickness.